If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (24x + -2) + (25x + -8) = 118 Reorder the terms: (-2 + 24x) + (25x + -8) = 118 Remove parenthesis around (-2 + 24x) -2 + 24x + (25x + -8) = 118 Reorder the terms: -2 + 24x + (-8 + 25x) = 118 Remove parenthesis around (-8 + 25x) -2 + 24x + -8 + 25x = 118 Reorder the terms: -2 + -8 + 24x + 25x = 118 Combine like terms: -2 + -8 = -10 -10 + 24x + 25x = 118 Combine like terms: 24x + 25x = 49x -10 + 49x = 118 Solving -10 + 49x = 118 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 49x = 118 + 10 Combine like terms: -10 + 10 = 0 0 + 49x = 118 + 10 49x = 118 + 10 Combine like terms: 118 + 10 = 128 49x = 128 Divide each side by '49'. x = 2.612244898 Simplifying x = 2.612244898
| 3n^2+6n+18=0 | | 49m^2-36/25=0 | | 49m^2-36/25= | | 5x-2y=-50 | | 13+.25a=-3 | | m+11=20 | | 8x+6x=10 | | 4x-14*3=x+7*3 | | 2m-7=8-3 | | (7x+26)+(10x-25)=138 | | 15/x=90/7 | | .14x+26=.71x-22 | | 4w+1w+3w-7= | | 15/x=7/90 | | log(33-3x^3)=2log(5-x) | | 3(x-(3-2x)+5)=5(x+4) | | 13x-14=0 | | 6(x-2)-4(x+3)=0 | | 2(x-1)-3(x-2)+4(x-3)=0 | | 4/9=24/3x-6 | | -16-7n=-21n^2+3n | | 63+5y-20=15y-13-2y | | (7b-7)-2(3b+2)=-6 | | 5y+n=m | | -3.9x-1=-3.5x+3 | | 3/4n-(-16)=28 | | 29xy-3x= | | 2(2x-2)-2(3-4z)=4 | | x=2.857142857+0.1428571429y | | 6k^2-48k=-42 | | -.75x+11=-130 | | 7(4x+8)=-224 |